HUBUNGAN STRES KERJA TERHADAP KUALITAS TIDUR PADA PERAWAT YANG MERAWAT PASIEN COVID-19 DI RSU ROYAL PRIMA - Ahmad Rafli Bintang; Adhayani Lubis; Sri Wahyuni Nasution (Gorontalo State University, 2021)
Background: Coronavirus Disease-19 (COVID-19) is a disease that occurred due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Since first time detected in Wuhan at the end of 2019, and declared as a pandemic in 11 February 2020 by World Health Organization/WHO, at least 222 million cases have been confirmed with more than 4,5 million deaths by COVID-19. Unpreparedness of healthcare system and government policy toward this pandemic resulted in workload increases uncontrollably for healthcare workers. Overwhelming workload in the healthcare sectors also affected healthcare workers, include nurses, which experienced mental health problem. Mental health problem such as depression, anxiety, frustration, and emotional instability become common in health care workers. This multiple mental health problem in addition of increased workload resulted in severe exhaustion along with sleeping problem, by the quality or quantity of the sleep. Method: This study is an analytic study with cross-sectional approach. Data collection conducted by using questionnaire. Result: Work stress level have a correlation with the quality of sleep with correlation value 0,406 (p greater than0,005), which is a moderate corelation. Conclusion: Stress level affected the quality of sleep in the nurses that care for COVID-19 patients, where the quality of sleep worsens along with increase of stress level.